LAPANG MOCAF school as a method to improve the economy of rural communities: A study case in Sumurup Village, Trenggalek Indonesia / Isnaini Rizkyah ... [et al.] - Rizkyah, Isnaini; Pandin, Moses Glorino Rumambo; Waloejo, Christrijogo Sumartono; Sunyowati, Dina (2021)
Indonesia experiences many disasters, moreover during pandemic Covid-19 (Waloejo et al., 2021; Pandin et al., 2021; Pramukti et al., 2020; Prakoeswa et al., 2021). Indonesia must prepare for emergency food to face many disasters. One of the potential local foods for emergency food is Cassava plants. According to the Central Statistics Agency, the production value of cassava agricultural products in Indonesia reached 24.08 million (Badan Pusat Statistik, 2015). Cassava management is easy because the growth of cassava plants is not affected by the season and can grow both in the highlands and the lowlands (Salim, 2011). However, based on the data, cassava cannot become a commodity with a high selling price. It can even be said that it cannot be a substitute for rice. It happens in Sumurup Village, Dam Subdistrict, Trenggalek Regency which most residents are farmers.